Relato de experiência da monitoria na disciplina Laboratório de Química Orgânica l: a importância da monitoria no processo de ensino-aprendizagem - MEDEIROS, Paulo Breno da Silva (2023)
This work aimed to report the experience in academic monitoring by the PGRADMONITORING program in the discipline laboratory of organic chemistry l, taught to the degree in chemistry at the Federal University of Pará UFPA, Campus Ananindeua, in the year 2022, academic semester 2022.3. The activities were carried out in the UFPA chemistry laboratory, where the monitor, through the difficulties and challenges encountered in the course of the discipline, helped the students in laboratory practices of extraction of fixed and volatile oils, as well as in the verification of secondary metabolites. At the end of the activities developed by the students, reports were prepared where the students presented their laboratory practices and their results obtained in the experiments, the study also sought to discuss the concepts obtained by the monitored in the discipline and the importance of the monitor as a link between the students and the teaching professor of the discipline, reaffirming the fundamental role of the monitoring program in the teaching-learning process acquired by the monitor within the program.